TRAINING AND IMPLEMENTATION OF THE SRIKANDI BACK-UP APPLICATION BASED ON THE ELECTRONIC FILING SYSTEM - Rosita; Cindy A. C; M. Ramzy F; M. Rizky R; Dinar K. P; Silvana O; Munparidi; Ria R; Hamdan S; Yusleli H (Jurnal Pengabdian Bangsa, 2025)
This community service activity aims to assist the Plantation Service of South Sumatra Province in addressing archive management challenges due to limited and often unstable internet connectivity. The primary archival management application in use is SRIKANDI, which relies on internet access. To mitigate the risks associated with this limitation, a backup system was developed using a simplified Microsoft Access-based Electronic Filing System (EFS) that operates offline. The community service project involved several phases: needs analysis, system design, staff training, implementation, and evaluation. Results showed that the backup system's features effectively supported archival management at the agency, improved retrieval efficiency, and enhanced data resilience against technical disruptions. Staff participating in the training quickly grasped and successfully operated the application.